Reflection of Young Martyr Kanaklata Barua and the Dependability of Assamese Women in India’s Freedom Movement - Guptajit Pathak (The Creative Launcher, 2016)
A teenage girl, who turned freedom fighter jumped into India’s Independence Movement against British, sacrificed her life during the Quit India Movement of 1942 and became a martyr at just 17 is none other than Kanaklata Barua. She was the daughter of Krishna Kanta Barua and Karneshwari Barua of Barangabari of Darrang District of Assam on 22nd December, 1926. She was Granddaughter of Ghana Kanta Barua. Ghana Kanta Barua was known for his hunting skills and thus was popular as Gahana Chikari or Ghana the Hunter. Kanaklata Barua lost her mother and father when she was 5 and 13 respectively. She was compelled to leave school from third standard as she had to take care of her younger siblings. The ancestors of Kanaklata Barua belong to the kingdom of Dolakharia Barua of the former state of Ahom and they gave up the title of Dolakharia and retained the title ‘Barua’. Kanaklata Barua became the first martyr of 1942 revolution. She is referred as ‘Shaheed’ or ‘martyr’ and ‘Birbala’ as she had been hardheartedly shot dead by police firing.